PERANCANGAN MOLD HANGER UNTUK PRODUK BERBAHAN LIMBAH PLASTIK PET - Kemal Asfari Hadyanto (2021)
The use of plastic is almost comprehensive in every aspect of human life, from food, medicine, clothing, and even vehicles. The use of plastic waste can cause various problems, one of which is environmental pollution. Therefore, waste, especially plastic, needs to be reprocessed into useful and valuable products. One solution that can be done is to design products made from plastic waste such as Hangers with the Injection Molding method. Therefore, in this study, a Mold Hanger was designed for products made from PET plastic waste with the aim of reducing and increasing the value of plastic waste. This research was conducted by designing Hanger and Mold Hanger products, as well as simulating the Hanger strength test and Mold Flow Hanger simulation. Based on the research that has been done, the design of the Mold Hanger with dimensions of 250x400 mm, weight 16.5 kg, thickness of each cavity & core is 30 mm, and uses a material in the form of Aluminum Alloy 7075 T6. Selected based on faster machining process, lighter weight, and relatively small volume expansion. While the results of the Mold Flow simulation show that the required injection pressure and clamping force are 32.9 Mpa and 25.6121 tons with a cycle time of 50.17 seconds.